Pengaruh Atribut Influencer Nagita Slavina Terhadap Niat Pembelian Produk Ms Glow Pada Influencer Marketing Di Media Sosial : Mediasi Peran Karakteristik - Krissianta, Octalavida Maharani; Febrianta, Mochammad Yudha (eProceedings of Management, 2024)
This study aims to determine how the influence of influencer attributes owned by Nagita Slavina has on the purchase intention of MS Glow products. This study uses a quantitative research method using a purposive sampling technique, namely the sampling method using certain considerations. Data was obtained by distributing questionnaires to social media users who know influencer Nagita Slavina and MS Glow beauty products. In this study, the samples obtained were 393 respondents with data collection instruments, 31 question items on the questionnaire from the 7 constructs used. Data were analyzed using the Structural Equation Model (SEM) method with the Partial Least Square (PLS) program using SmartPLS 3.0 software. This study found the influence of influencer marketing attributes and characteristics to have a positive influence on consumer purchase intentions. The survey shows that the marketing strategy using the influencer marketing approach needs to be adjusted based on the influencer's attributes and the characteristics of the influencer himself. The findings in this study contribute to the literature on marketing communications, especially for influencer marketing research. This research also practically provides recommendations for businesses, especially in the beauty industry, on how to carry out marketing strategies using a positive influencer marketing approach to increase consumer purchase intentions. Keywords-influencer marketing, influencer attributes, characteristics, purchase intention